Dying for the group: Towards a general theory of extreme self-sacrifice - Whitehouse, H (Cambridge University Press, 2018)
Whether upheld as heroic or reviled as terrorism, throughout history people have been willing to lay down their lives for the sake of their groups. Why? Previous theories of extreme self-sacrifice have highlighted a range of seemingly disparate factors such as collective identity, outgroup hostility, and kin psychology. This paper attempts to integrate many of these factors into a single overarching theory based on several decades of collaborative research with a range of special populations, from tribes in Papua New Guinea to Libyan insurgents, and from Muslim fundamentalists in Indonesia to Brazilian football hooligans. These studies suggest that extreme self-sacrifice is motivated by 'identity fusion', a visceral sense of oneness with the group resulting from intense collective experiences (e.g. painful rituals or the horrors of frontline combat) or from perceptions of shared biology. In ancient foraging societies, fusion would have enabled warlike bands to stand united despite strong temptations to scatter and flee. The fusion mechanism has often been exploited in cultural rituals, not only by tribal societies but also in specialized cells embedded in armies, cults, and terrorist organizations. With the rise of social complexity and the spread of states and empires, fusion has also been extended to much larger groups, including doctrinal religions, ethnicities, and ideological movements. Explaining extreme self-sacrifice is not only a scientific priority but also a practical challenge as we seek a collective response to suicide terrorism and other extreme expressions of outgroup hostility that continue to bedevil humanity today.